Analisis Faktor yang Mempengaruhi Minat Nasabah Memilih Produk Tabungan Wakaf di Bank CIMB Niaga Syariah Cabang Samarinda - Irma Yuliani (Ekonomis: Journal of Economics and Business, 2022)
This type of research is a field research that is a study conducted systematically by raising the data in the field. The purpose of this study is to determine the Marketing Strategy and the factors that influence the customer's interest in choosing a waqf savings product and its mechanism and process at the Samarinda Branch of CIMB Niaga Syariah Bank for consideration in decision making. The nature of this research is descriptive qualitative. The study used observation, interview and documentation techniques with several key customers of waqf savings and related bank management / parties. The research uses factor analysis of Miles and Hubberman analysis techniques and triangulation. The results showed that the marketing strategy undertaken by Bank CIMB Niaga Syariah Samarinda Branch used STP (Segmentation, targeting, and Positioning). Segmentation is to divide customers based on social strata class, income level and occupation, positioning which offers sharia values through waqf savings products as one of the superior products that is unique, superior and provides benefits for customers and recipients of waqf.